2010
DOI: 10.1007/s10856-010-4016-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of human osteoblast adhesion to a thermally oxidized γ-TiAl intermetallic alloy of composition Ti–48Al–2Cr–2Nb (at.%)

Abstract: Ti–48Al–2Cr–2Nb (at.%) (γ-TiAl), a gamma titanium aluminide alloy originally designed for aerospace applications, appears to have excellent potential as implant material. Thermal treatment of γ-TiAl renders this alloy extremely corrosion resistant in vitro, which could improve its biocompatibility. In this study, the surface oxides produced by thermal oxidation (at 500°C, and at 800°C for 1 h in air) on γ-TiAl were characterized by X-ray photoelectron spectroscopy (XPS). hFOB 1.19 cell adhesion on thermally ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 32 publications
2
20
0
1
Order By: Relevance
“…After 10 days of incubation, a confluent multilayer of cells was observed on all the MAO treated surfaces, untreated γTiAl and Ti-6Al-4V disks and glass coverslips. SEM images of the cells cultured on the Ti alloy surfaces, clearly indicate that hFOB 1.19 cells exhibited normal growth on the surfaces of both MAO γTiAl and Ti-6Al-4V disks, similar to earlier reports [20,26]. The cell multilayer observed, was constituted by elongated and polygonal cells.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…After 10 days of incubation, a confluent multilayer of cells was observed on all the MAO treated surfaces, untreated γTiAl and Ti-6Al-4V disks and glass coverslips. SEM images of the cells cultured on the Ti alloy surfaces, clearly indicate that hFOB 1.19 cells exhibited normal growth on the surfaces of both MAO γTiAl and Ti-6Al-4V disks, similar to earlier reports [20,26]. The cell multilayer observed, was constituted by elongated and polygonal cells.…”
Section: Resultssupporting
confidence: 87%
“…Recently the potential of gamma titanium aluminide (γTiAl) as a biomaterial for orthopedic applications has been extensively researched and promising indicators have been observed [1720]. It is believed that this potential biomaterial potential for implant applications can be further enhanced by modifying the surface of γTiAl by the MAO technique.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, when oxidized at 800°C Ti-6Al-4V showed a decrease in cell attachment in comparison with gamma-TiAl on which recent studies for biocompatibility have demonstrated a good response of the metal analyzed both in vitro and in vivo 15 .…”
Section: Introductionmentioning
confidence: 80%
“…%) [17][18][19] . Oxidation of this alloy (henceforth also referred to as gamma-TiAl) at 500°C and 800°C has shown contrasting behavior in terms of cytotoxicity of the oxidized surfaces [20] . A number of other studies have characterized wear behavior of both gamma titanium aluminides and their oxidized surfaces [21][22][23] albeit under rotating pin-on-disk configurations, although it is obvious that reciprocatory motion is more representative of the actual micro-motion at the bone-implant interface.…”
Section: Introductionmentioning
confidence: 99%